Biodiversity loss impacts top-down regulation of insect herbivores across ecosystem boundaries - Wyckhuys, Kris A.G.; Pozsgai, Gabor; Ben Fekih, Ibtissem; Sanchez-Garcia, Francisco J.; Elkahky, Maged (The Science of the total environment, 2024)
Biodiversity loss, as driven by anthropogenic global change, imperils biosphere intactness and integrity. Ecosystem services such as top-down regulation (or biological control; BC) are susceptible to loss of extinction-prone taxa at upper trophic levels and secondary ‘support’ species e.g., herbivores. Here, drawing upon curated open-access interaction data, we structurally analyze trophic networks centered on the fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) and assess their robustness to species loss. Tri-partite networks link 80 BC organisms (invertebrate or microbial), 512 lepidopteran hosts and 1194 plants (including 147 cultivated crops) in the Neotropics. These comprise threatened herbaceous or woody plants and conservation flagships such as saturniid moths. Treating all interaction partners functionally equivalent, random herbivore loss exerts a respective 26 % or 108 % higher impact on top-down regulation in crop and non-crop settings than that of BC organisms (at 50 % loss). Equally, random loss of BC organisms affects herbivore regulation to a greater extent (13.8 % at 50 % loss) than herbivore loss mediates their preservation (11.4 %). Yet, under moderate biodiversity loss, (non-pest) herbivores prove highly susceptible to loss of BC organisms. Our topological approach spotlights how agriculturally-subsidized BC agents benefit vegetation restoration, while non-pest herbivores uphold biological control in on- and off-farm settings alike. Our work underlines how the on-farm usage of endemic biological control organisms can advance conservation, restoration, and agricultural sustainability imperatives. We discuss how integrative approaches and close interdisciplinary cooperation can spawn desirable outcomes for science, policy and practice. [Display omitted] •Eighty FAW parasitoids or entomopathogens are indirectly linked to 1194 genera of plants.•On-farm biological control is inherently tied to off-farm plant and animal biodiversity.•Agriculturally-subsidized natural enemies shape off-farm restoration outcomes.•Herbivore loss disproportionately impacts top-down regulation across habitat boundaries.•Conservation biology, restoration ecology and biological control domains are to be entwined.